Construction of Multidimensional Practice Platform Based on Cultivation of Innovative Ability of Rehabilitation Therapy Professional Students - Li XIAO; Juying XIE; Shanxi WANG; Ziteng OUYANG (康复学报)
Rehabilitation therapy is a practical major, which has a high demand for professional skills and professional quality. The students not only need master the basic theory of rehabilitation therapy, but also need some innovative ability. In this paper, Research of the construction of multidimensional practice platform was carried out, so as to promote the students' ability of innovative and practice of rehabilitation therapy professional students.